2004
DOI: 10.1128/iai.72.5.2956-2963.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of Macrophages in Host Resistance to Group A Streptococci

Abstract: Macrophages provide the first line of defense against invading pathogens. The aim of this study was to determine the role of macrophages during infection with group A streptococci (Streptococcus pyogenes) in mice. Here, we report that resident macrophages can efficiently take up and kill S. pyogenes during in vivo infection, as demonstrated by immunofluorescence and electron microscopy, as well as colony counts. To evaluate the contribution of macrophages to the resolution of experimental infection with S. pyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 40 publications
4
127
0
3
Order By: Relevance
“…Remarkably little information is available also about the signaling pathways triggered by GAS in infected innate immune cells that are known to be required for defense against GAS (22). Here we show that GAS activates p38 MAPK, NF-B, TNF␣, and IL-6 production in infected bone marrow-derived mouse macrophages (BMDMs).…”
Section: Bacterial Pathogens Are Recognized By the Innate Immune Systmentioning
confidence: 87%
See 1 more Smart Citation
“…Remarkably little information is available also about the signaling pathways triggered by GAS in infected innate immune cells that are known to be required for defense against GAS (22). Here we show that GAS activates p38 MAPK, NF-B, TNF␣, and IL-6 production in infected bone marrow-derived mouse macrophages (BMDMs).…”
Section: Bacterial Pathogens Are Recognized By the Innate Immune Systmentioning
confidence: 87%
“…Activation of both NF-B and p38 MAPK was shown in numerous studies to be essential for production of proinflammatory cytokines (38 -42). Furthermore, macrophages express all components of the TLR signaling cascade and are known to be required for defenses against GAS infection (22). We first compared the activation of p38 MAPK and NF-B in WT and TLR2 Ϫ/Ϫ BMDMs, since many Gram-positive pathogens are recognized by this receptor.…”
Section: Gas Activates Inflammatory Signaling Independently Of Tlr2 mentioning
confidence: 99%
“…Depletion of the monocyte/macrophage subpopulation was achieved by using carrageenan as described previously (16,17). Briefly, mice were injected i.p.…”
Section: Sepsis Studiesmentioning
confidence: 99%
“…Specifically, we wanted to test the hypothesis that effective innate responses in the early stages of infection is directly associated with resolution of GAS infection, and better outcome of GAS sepsis. We based our hypothesis on studies from our group and other groups that showed that neutrophils (Voyich et al, 2004;Buchanan et al, 2006;Nilsson et al, 2006;Soehnlein et al, 2008a;Navarini et al, 2009), macrophages (Goldmann et al, 2004a;Thulin et al, 2006;Goldmann et al, 2009), NK cells (Goldmann et al, 2005b;Takahashi et al, 2007) and dendritic cells (Loof et al, 2008;Cortes and Wessels, 2009;Yong et al, 2009), each play an important role in streptococcal infections according to the site and the stage of infection. We started our cellular dissection by examining the role of neutrophils in differential susceptibility to GAS sepsis.…”
Section: Chapter 5 Analysis Of Cellular Populations Modulating Diffementioning
confidence: 99%
“…Neutrophils and macrophages play an important role in modulating host responses to GAS sepsis (Goldmann et al, 2004a;Voyich et al, 2004;Medina and Lengeling, 2005). To dissect the role of these cells, we examined the effect of depleting them in vivo on differential mice susceptibility to severe GAS sepsis.…”
mentioning
confidence: 99%